Extracellular matrix dysregulation in PCOS: pathogenesis, therapeutic strategies, and innovative technologies - Yunxi Liu; Jialei Zhu; Yingli Yang; Zhengyun Chen; Yong Zhou; Weidong Fei; Xian Zhang; Yongquan Zheng (Journal of Biological Engineering)
Abstract Polycystic ovary syndrome (PCOS), the most common endocrine disease in women of reproductive age, severely impacts female fertility due to chronic anovulation and currently lacks effective clinical treatment strategies. The extracellular matrix (ECM) is a three-dimensional, non-cellular framework comprising molecules such as collagens, elastin, and laminin, which support the ovarian structure and provide extracellular signals to cells. Changes in ECM localization and composition can disturb local biochemical pathways, impair folliculogenesis, and reduce the fertility of women. This paper explores innovative therapeutic approaches for PCOS by investigating the mechanisms underlying PCOS pathogenesis due to ECM dysregulation. This includes ECM deposition-induced inflammation and fibrosis, impaired ECM degradation, altered mechanical forces in ECM remodeling, and disrupted interactions between granulosa cells and the ECM. In the second part, we present therapeutic strategies informed by these pathogenic mechanisms, integrating insights from basic and clinical research. More importantly, this paper introduces innovative therapies for POCS that regulate ECM. These therapeutic strategies represent future development directions. In the final section, we summarize the advantages, potential challenges, and prospects of ECM-based treatments for improving fertility in PCOS. Overall, this review underscores the emerging significance of ECM-targeted interventions in unraveling PCOS pathophysiology and paves the way for the development of more precise and effective fertility-preserving therapies.